BRUNA SCHUMAKER SIQUEIRA HOMEOSTASE GLICÊMICA EM RATOS COM OBESIDADE HIPOTALÂMICA: INFLUÊNCIAS INTESTINAIS, VAGAIS E ESPLÊNICAS - Siqueira, Bruna Schumaker (2025)
Glycemic homeostasis relies on the balance between intestinal glucose absorption, insulin secretion, and peripheral insulin sensitivity. In hypothalamic obesity induced by neonatal treatment with monosodium glutamate (MSG), this balance is disrupted, frequently accompanied by increased vagal tone. Bombesin-like peptides modulate incretin secretion and endocrine pancreatic function and can also activate vagal pathways. The vagus nerve regulates both metabolic and inflammatory responses, processes that involve splenic participation. Glucose uptake, intestinal motility, and inflammation are influenced by ionotropic purinergic receptors (P2X), whose roles remain unexplored in MSG-induced obese rats. Objective: To characterize the glycemic profile of MSG-obese rats by investigating intestinal mechanisms of glucose absorption, the involvement of P2X receptors, insulin secretory control, and the contributions of vagal and splenic pathways. Methods: Neonatal male Wistar rats received MSG (4 g/Kg) to induce obesity, while control animals (non-obese) received an equimolar saline solution. Experimental groups were organized into three designs: (i) At 70 days of age, the effects of a bombesin analog (Br-b) were evaluated during oral glucose tolerance tests (OGTT) and on isolated pancreatic islets; (ii) At 148 days, OGTT, intestinal expression of glucose transporters (SGLT-1, GLUT-2, and GLUT-12), and purinergic receptors (P2X4 and P2X7), as well as insulin secretion in isolated pancreatic islets, were assessed; (iii) Also at 148 days, MSG-obese rats previously subjected (at 60 days) to subdiaphragmatic vagotomy and/or splenectomy were evaluated regarding glucose tolerance, insulin secretion, vagal nerve activity recordings, and endocrine pancreas histology. At euthanasia, biometric and adiposity measures were collected, along with plasma analyses for glucose, triglycerides, total cholesterol, insulin, GLP-1, and IL-10. Insulin sensitivity and β-cell function indices were also calculated. Results: MSG-obese rats showed increased adiposity, hyperinsulinemia, insulin resistance, and reduced GLP-1 levels. Pre-administration of the Br-b analog improved OGTT performance in both MSG-obese and control rats, with limited insulinotropic effects on pancreatic islets from obese animals. In MSG- obese rats, the glycemic peak occurred later, potentially due to altered intestinal expression of glucose transporters (↑SGLT-1 and GLUT-12; ↓GLUT-2) and P2X receptors (↑P2X7; ↓P2X4). Vagotomy reduced visceral fat, improved insulin sensitivity, and enhanced pyruvate tolerance. Splenectomy decreased vagal activity, suggesting bidirectional interactions between the vagus nerve and spleen, which impacted pancreatic lipid deposition and glucose-stimulated insulin secretion. Conclusions: MSG-induced hypothalamic obesity impairs glycemic homeostasis through mechanisms involving insulin resistance, hyperinsulinemia, and altered responsiveness to bombesin-like peptides. Changes in the distribution profile of intestinal glucose transporters (SGLT-1, GLUT-2, and GLUT-12) and ionotropic purinergic receptors (P2X4 and P2X7) may contribute to delayed glucose absorption. Finally, vagal and splenic interactions modulate adiposity, insulin sensitivity, and pancreatic β-cell secretory function in MSG-obese rats.